COMPARISON OF SAFETY AND EFFICACY OF ORAL PROGESTERONE WITH LEVONORGESTREL INTRAUTERINE SYSTEM IN MANAGEMENT OF DYSFUNCTIONAL UTERINE BLEEDING - ANDLEEB , G; RASHEED , A; MUZAFFAR , A; MALIK , SA (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Department of Obstetrics and Gynaecology, Nishtar Medical Hospital, Multan, to compare the safety and efficacy of oral progesterone and levonorgestrel-releasing intrauterine system (LNG-IUS) for the management of DUB. The study was conducted on 90 patients who fulfilled the inclusion criteria. Participants were randomly divided into groups A (LNG-IUS) and B (oral progesterone). The primary outcomes were Pictorial blood loss assessment chart (PBAC) scores. Secondary outcomes were the evaluation of adverse effects and Hb levels. A comparison of the mean PBAC score showed that LNG-IUS significantly reduced PBAC scores (P< 0.0001). Comparison of post-treatment HB levels showed that LNG-IUS significantly increased Hb level, and the difference between both groups was statistically significant (P< 0.0001). After 6 months, the incidence of adverse effects in group B was 60%, while in group A was 40%. However, hypomenorrhea was more prevalent in group A. It can be concluded that LNG-IUS is a more effective and safe treatment choice for Dub compared to oral progesterone.